Application of a Reusability Approach in Simulation of Heritage Buildings Performance, Taif- Saudi Arabia - Ali Alzaed (Advances in Science, Technology and Engineering Systems Journal, 2021)
The main purpose of this paper is to present a reusability approach that helps the designer to assess the best practice to restore a heritage building. Based on the literature review, the reusability process and attributes was used as a method to restore the heritage building. Considering these approaches helps the designer to achieve useful results in terms of the built environment and building performance; moreover, it helps the designer to identify the suitable new usage of the building. Also, the designer validated the building performance through using the TAS to assess the thermal comfort of the building after using passive techniques and design restorations. The obvious finding was the successful achievement through considering this approach and decreasing the interior temperature two degrees. This study can be assessed as one of the optimistic practices that considered the sustainability dimensions during the restoration process, as well as improving the thermal comfort of the building for the end user. The research paper provides a useful understanding of designers, restorers and researchers.
Keywords: Heritage building; Reusability process and attributes; Thermal comfort; Green restoration